Prakriyāsarvasvaṃ : savyākhyam - Nārāyaṇabhaṭṭapāda (Pustakaprakāśanavibhāgaḥ, Keralaviśvavidyālayaḥ, 1973)
Commentary, with two supercommentaries, on Pāṇini's Aṣṭādhyāyī, aphoristic work on Sanskrit grammar.